RESEARCH AND DEVELOPMENT BARRIERS IN MANAGEMENT AND BUSINESS AREA: STRATEGIC MANAGEMENT OVERVIEW - Kumaratih Sandradewi; harsanto harsanto; Andriani Kusumaningrum; Afu Ichsan Pradana (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Research and Development has become a reality of needs that must be met by business organizations and non-profit organizations. Business actors as organizations and as part of the industrial community in achieving sustainability are faced with how to transform in the digital transformation era and the era of the covid-19 pandemic in the form of real efforts through holistic strategic changes and new and contemporary ways of thinking. With the shift in business assumptions from conventional business to digital business so that the innovation paradigm is open, with the support of Research and Development assuming that knowledge that is efficient, high quality and widely distributed to form a digital ecosystem to become a " digital highway " with a collaborative spirit to build is strategic management quick reaction to answer the company's organizational problems. Keywords: Research, development, strategic management, information technology